Baggage Handling Unit Handling and Constraints during the Loading Unloading Process to Achieve On Time Performance at PT Kokapura at Ahmad Yani Airport Semarang - Abdul Rozak; Elnia Frisnawati (QISTINA: Jurnal Multidisiplin Indonesia, 2023)
Baggage handling has an important role, this is because handling is related to passenger satisfaction. Baggage handling must be managed properly to avoid mistakes such as loss and damage. Baggage handling is the process of servicing passenger baggage at the departure station to the arrival station. The baggage handling process must be carried out carefully, conscientiously, caringly and carefully so that timeliness (OTP) can be achieved. This study uses qualitative methods and the data produced is in the form of descriptions. The primary data in this study were the results of interviews with the load master, ramp and porter officers. As for the secondary data in this study in the form of literature and previous research. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques were carried out in the form of data collection, data reduction, data presentation, and conclusions. The handling carried out during the loading unloading process is preparing documents such as loading check lists, loading instructions, stowing, and coordinating with load control or FOO and porters. While the obstacles during the loading and unloading process to achieve OTP include weather factors, aircraft engine damage, lack of supporting facilities and lack of porter personnel.